Geopolitical interest of Iran in Central Asia (International relations and international law Journal, 2019)
The purpose of this study is to carry out the analysis of the external IRI policy in Central Asia in the context of new geopolitical configuration, to study the economic and political aspects of the strengthening of Iran in the region, to identify its features and the most important aspects of bilateral relations between Kazakhstan and Iran as well as the development patterns, to analyze the objective socio-economic situation in the region of Central Asia in the context of formation of a new geopolitical situation after the cancellation of sanctions against Iran. This paper is based on the use of the geo-political importance of this subject and is supported by the papers of Kazakh, Russian and foreign authors. The following general scientific methods and techniques are used in this paper: the new functional analysis, the structural analysis, the scientific abstraction, the qualitative expert estimates, the quantitative estimates, the comparative analysis. The changes in the geopolitical situation in Central Asia after the cancellation of the US sanctions against Iran are studied in this paper. The role of Iran in the region and its importance are defined based on the strengthening of the integration processes and creation of the EAEC. The role of Kazakhstan as one of the leaders in the framework of modern international relations in Central Asia is also studied in this paper. The recommendations on improvement of the influence and, in particular, on foreign policy decisions of the Republic of Kazakhstan are given.Key words: Geopolitics, regional cooperation, internal cooperation, diplomacy, foreign policy initiatives, the main actors.